Azerbaijan Republic : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Azerbaijan Republic. (IMF Staff Country Reports; Country Report ;, 2004)
Macroeconomic performance continues to be strong, with double-digit real gross domestic product growth and low inflation. All quantitative and structural performance criteria have been met. Significant progress has been made in converting quasi-fiscal subsidies to fiscal subsidies. The government acknowledges the importance of developing a long-term oil revenue management strategy. The government will continue comprehensive structural reforms, including adoption of an automatic price adjustment mechanism for domestically sold oil and gas product prices, and adoption of the banking system and central bank laws.